Polar cycloolefin copolymer as well as preparation method and application thereof
By combining late-transition nickel catalysts with late-transition palladium catalysts, the problem of lack of polar groups in traditional cycloolefin copolymers was solved, and the efficient preparation of polar cycloolefin copolymers was achieved, thereby enhancing their application potential in high-end fields.
Patent Information
- Application Number
- CN202511054623.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-10-10
AI Technical Summary
Traditional cycloolefin copolymers lack polar groups, resulting in non-polarity and low surface energy on their surfaces, hindering their application in high-end fields. Existing modification methods are cumbersome or have low copolymerization efficiency and high catalyst requirements.
A late transition nickel catalyst is combined with a late transition palladium catalyst to carry out a copolymerization reaction of ethylene and a polar cycloolefin monomer in an inert solvent through the catalyst composition to prepare a polar cycloolefin copolymer. The synergistic effect of the Ni and Pd active centers is utilized to improve the catalytic activity and polar group tolerance.
The polar group insertion rate of the polar cycloolefin copolymer is effectively improved, the preparation process is simplified, and the catalytic activity and polar group content of the copolymer are improved.
Smart Images

Figure BDA0005524018450000021 
Figure BDA0005524018450000031 
Figure BDA0005524018450000041
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polyolefins, and in particular to a polar cycloolefin copolymer and a preparation method and application thereof. Background Art
[0002] Cyclo-Olefin Copolymer (COC) is a polymer material produced by the copolymerization of cycloolefin monomers with ethylene or α-olefins. This material typically appears as colorless particles or flakes. The introduction of cycloolefin monomers creates a certain amount of internal stress within the cyclic structure of the molecular structure, which optimizes the crystallinity of traditional polyolefins, thereby enhancing transparency. COC not only exhibits high transparency and heat resistance, but also combines the advantages of both amorphous and crystalline copolymers, such as low water absorption, excellent optical properties, good biocompatibility, and superior processing properties. These properties make COC an ideal material choice for applications such as electronic displays and pharmaceutical packaging.
[0003] Polar cycloolefin copolymers, with their unique performance advantages, have shown strong market demand in multiple high-end fields. For example, with the further development of the electronic information industry, COC is required to have a certain degree of adhesion to materials such as Si, Cu, and Al to facilitate subsequent product applications. However, the traditional COC structure does not have polar groups, and its surface has non-polar and low surface energy properties, which hinder its application. To this end, researchers have adopted three strategies: post-treatment, pre-treatment, and direct copolymerization to give COC polar groups to functionalize it. The post-treatment method for preparing polar COC is mainly to use a cycloolefin monomer containing two double bonds to copolymerize with an olefin, and then use the residual double bonds in the copolymer for post-treatment to convert them into polar groups. Because the polar groups are generated through post-treatment, they will not affect the catalytic activity. The resulting copolymer has a high content of polar groups, but the steps are cumbersome (Macromol Rapid Comum., 2005, 26, 1208). Pre-treatment method is when metallocene etc. carries out olefin coordination polymerization to heteroatom sensitive catalyst, because polar group can form stable complex with catalyst or promotor complexing, reduce reactive behavior, take polar group to be protected in advance.This method can also obtain the multipolymer of higher polar group, but copolymerization efficiency is low (MacromolChemPhys.,2004,205,308).And direct polymerization method can obtain high polar group content, can simplify reactions steps again, can also have the effective means of higher copolymerization activity, but direct polymerization method has high requirements on catalyst, is usually difficult to meet the efficient insertion of polar cycloolefin, needs to do further research. Summary of the Invention
[0004] The purpose of the present invention is to provide a polar cycloolefin copolymer and its preparation method and application in order to solve the above problems.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] A method for preparing a polar cycloolefin copolymer comprises the following steps: using ethylene and a polar cycloolefin monomer as raw materials in an inert solvent, and carrying out a copolymerization reaction using a catalyst composition, wherein the catalyst composition comprises a late transition nickel catalyst, a late transition palladium catalyst, and a co-catalyst;
[0007] The structural formula of the late transition nickel catalyst is shown in Formula C, and the structural formula of the late transition palladium catalyst is shown in Formula D:
[0008]
[0009] In formula C and formula D, X is chlorine or bromine, R1 to R9 are independently selected from H, C1 to C6 alkyl, C1 to C6 alkoxy, C6 to C 12 Aryl or halogen.
[0010] Furthermore, the C1-C6 alkyl group includes an alkyl group with a straight chain structure or a branched structure, for example, including but not limited to methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, pentyl or hexyl, preferably methyl, isopropyl, tert-butyl.
[0011] Furthermore, the C1-C6 alkoxy group includes a methoxy group, an ethoxy group, a n-propoxy group, an isopropoxy group, a n-butoxy group, an isobutoxy group, a tert-butoxy group, a pentyloxy group or a hexyloxy group.
[0012] Furthermore, C6-C 12 Aryl is a monovalent aromatic carbocyclic ring system having at least one aromatic ring or multiple fused rings wherein at least one ring is aromatic, for example, may be selected from phenyl, naphthyl or biphenyl.
[0013] Furthermore, the halogen is selected from F, Cl, Br, and I.
[0014] The present invention conducts a solution polymerization reaction on a polar cycloolefin monomer and ethylene. Both a late transition nickel catalyst and a late transition palladium catalyst use 6,7-dihydro-5H-quinoline-8-one as a skeleton and coordinate two active centers, Ni and Pd, respectively. The Ni-centered catalyst promotes the copolymerization of ethylene and cycloolefin, and the Pd-centered catalyst improves the tolerance of polar groups. Through the combined action of the catalyst combination, a polar olefin copolymer with a high insertion rate of the polar cycloolefin monomer is prepared.
[0015] As a preferred technical solution, in Formula C and Formula D, at least one of R1 to R9 is selected from H, C1-C6 alkyl or halogen.
[0016] As a preferred technical solution, in Formula C and Formula D, at least one of R1 and R9 is a C1-C6 alkyl or a halogen, and the halogen is selected from F, Cl, Br, and I.
[0017] As a preferred embodiment of the present invention, the late transition nickel catalyst is selected from any one of the following formulas C1 to C4, and the late transition palladium catalyst is selected from any one of the following formulas D1 to D4:
[0018]
[0019]
[0020] Wherein, X is chlorine or bromine.
[0021] Furthermore, the late transition nickel catalyst and the late transition palladium catalyst are prepared by reacting an α-diimine ligand represented by formula L with a nickel salt or a palladium salt in an anhydrous aprotic organic solvent under an anhydrous and oxygen-free environment.
[0022]
[0023] In formula L, R1 to R9 are as defined above.
[0024] The nickel salt and the palladium salt can be metal halides, such as chlorides or bromides, including but not limited to nickel bromide, nickel chloride, palladium chloride, and the like.
[0025] The catalyst can be prepared by conventional methods for synthesizing coordination compounds in the art: the α-diimine ligand and nickel salt or palladium salt are dissolved in an anhydrous aprotic organic solvent at a molar ratio of 1:1 to 4, and reacted in an anhydrous and oxygen-free environment. The specific reaction formula is as follows:
[0026]
[0027] Specifically, the ligand L prepared above and nickel salt or palladium salt are dissolved in an anhydrous aprotic organic solvent (for example, acetonitrile, toluene, dichloromethane) in a molar ratio of 1:1 to 4, and the anhydrous and oxygen-free environment is controlled. The reaction is carried out at a reaction temperature of 0 to 100° C. for 8 to 36 hours. After the reaction is completed, the reaction is filtered and washed 2 to 3 times, and the sample is placed in a vacuum drying oven to dry.
[0028] As a preferred embodiment of the present invention, the α-diimine ligand is selected from any one of the following compounds of Formula L1 to Formula L4:
[0029]
[0030]
[0031] Furthermore, the α-diimine ligand represented by Formula L is prepared by acid catalysis using a 6,7-dihydro-5H-quinolin-8-one derivative of the general structure represented by Formula I and an aniline derivative of the general structure represented by Formula II as raw materials. The specific reaction formula is as follows:
[0032]
[0033] In the 6,7-dihydro-5H-quinolin-8-one derivatives of the general structure shown in Formula I, R1-R6 can be the same or different groups, independently selected from H, C1-C6 alkyl, C1-C6 alkoxy, aromatic phenyl, aromatic naphthyl, aromatic biphenyl, halogen, etc. In preferred embodiments of the present invention, the 6,7-dihydro-5H-quinolin-8-one derivatives include 6,7-dihydro-5H-quinolin-8-one, 2-chloro-6,7-dihydro-5H-quinolin-8-one, 2-methyl-6,7-dihydro-5H-quinolin-8-one, etc.
[0034] The aniline derivative of the general structure represented by Formula II has a primary amine as the main skeleton, and R7-R9 can be the same or different groups, independently selected from H, C1-C6 alkyl, C1-C6 alkoxy, aromatic phenyl, aromatic naphthyl, aromatic biphenyl, halogen, etc. Preferably, a primary amine with an electron-donating effect is used as the amine raw material, and more preferably, a primary amine with an electron-donating group with a certain steric effect is used as the amine raw material. In an embodiment of the present invention, the aniline derivative is selected from aniline, o-methylaniline, 3,5-dimethylaniline, p-methylaniline, p-bromoaniline, 2-methylaniline, 2-tert-butylaniline, 2-phenylaniline, etc.
[0035] Furthermore, the preparation method of the α-diimine ligand of the present invention comprises the following steps: a 6,7-dihydro-5H-quinolin-8-one derivative and an aniline derivative are dissolved in a non-protonic polar organic solvent in a molar ratio of 1:1.1 to 2.5, and then a non-oxidizing organic strong acid is used as a catalyst (catalytic level) to react at 40 to 150° C. for 4 to 48 hours. The reaction temperature is preferably 80 to 120° C. and the reaction time is preferably 8 to 24 hours. After the reaction is completed, the solvent is removed from the mixture and purified to obtain the α-diimine ligand.
[0036] Preferably, the organic aprotic polar solvent is a commonly used solvent in the art, such as benzene, toluene, etc. The non-oxidizing organic strong acid can be a commonly used organic strong acid in the art, such as p-toluenesulfonic acid. The solvent can be removed by conventional methods in the art, such as rotary evaporation. The product can be purified by conventional methods in the art, such as recrystallization, column chromatography, etc.
[0037] As a preferred technical solution of the present invention, the molar ratio of the late transition nickel catalyst, the late transition palladium catalyst and the co-catalyst is 1:0.05-0.5:50-10000; preferably, the molar ratio of the late transition nickel catalyst, the late transition palladium catalyst and the co-catalyst is 1:0.08-0.25:200-6000; further preferably, the molar ratio of the late transition nickel catalyst, the late transition palladium catalyst and the co-catalyst is 1:0.1-0.2:200-3000.
[0038] As a preferred technical solution of the present invention, the inert solvent includes C6-C8 straight-chain alkanes, benzene and its derivatives, preferably benzene, toluene, xylene, chlorobenzene, hexane, pentane, etc.
[0039] As a preferred technical solution of the present invention, the polar cycloolefin monomer is a cycloolefin with a polar group, including but not limited to 5-norbornene-2-carboxylic acid methyl ester, 5-norbornene-2-ol, 5-norbornene-2-methylamine, 5-norbornene-2,3-dicarboxylic acid methyl ester, 5-norbornene-2-carboxylic acid, 5-methoxy-2-norbornene, etc.
[0040] As a preferred technical solution of the present invention, the co-catalyst includes alkylaluminoxane, more preferably methylaluminoxane, modified methylaluminoxane, diethylaluminum chloride, isobutylaluminoxane and the like.
[0041] As a preferred technical solution of the present invention, during the copolymerization reaction, a temperature-controlled pressure-resistant reactor is used as a reactor (for example, a stirred reactor with a heat exchange jacket), and the pressure in the reactor is controlled to be 0.1-10 MPa by ethylene, and the temperature is controlled to be 50-120°C; preferably, the pressure is 0.1-2 MPa, more preferably the pressure is 0.1-1 MPa, and the reaction temperature is preferably 50-80°C.
[0042] As a preferred technical solution of the present invention, the volume molar ratio of the inert solvent to the polar cycloolefin monomer is 1-10 L / mol, preferably 2-8 L / mol, and more preferably 4-6 L / mol;
[0043] As a preferred technical solution of the present invention, the molar ratio of the total amount of the late transition nickel catalyst and the late transition palladium catalyst relative to the polar cycloolefin monomer is 0.01% to 1%, preferably 0.01% to 0.1%, and more preferably 0.01% to 0.05%.
[0044] Furthermore, a polar cycloolefin copolymer is prepared using the above-mentioned preparation method.
[0045] The polar cycloolefin copolymer obtained above is used in the preparation of electronic product display materials and medical and pharmaceutical packaging materials.
[0046] Compared with the prior art, the present application has the following beneficial effects:
[0047] The present application provides a preparation process of polar cyclic olefin copolymer, which overcomes the problem of low insertion rate of polar cyclic olefin comonomer, and effectively obtains polar cyclic olefin copolymer with high comonomer content by using a combination of a late transition nickel-based catalyst and a late transition palladium-based catalyst. The specific mechanism is not very clear, and the inventors speculate that the mechanism is as follows: (1) coordination of N atoms in the catalyst skeleton structure with the metal center can improve the electronic structure of the metal center; (2) the catalyst with Ni as the active center can effectively improve the catalytic activity, and the catalyst with Pd as the active center has weak electrophilicity and can tolerate polar comonomer, the interaction of the two plays a synergistic effect, effectively promoting the copolymerization of ethylene and polar norbornene. DETAILED DESCRIPTION
[0048] The following description is provided to enable any person skilled in the art to practice the present application. The preferred embodiments in the following description are only examples of how the present application can be implemented, and are not intended to limit the scope of the present application. Those skilled in the art can think of other obvious modifications. The basic principles of the present application defined in the following description can be applied to other embodiments, modifications, improvements, equivalents and other technical solutions without departing from the spirit and scope of the present application. The instruments or reagents in the embodiments of the present application are not specified by the manufacturer, and are all conventional commercial instruments or reagents.
[0049] The main reagents used in the examples are specifically sourced as follows:
[0050] 6,7-Dihydro-5H-quinolin-8-one CAS: 56826-69-8, Anaspec
[0051] 2-Chloro-6,7-dihydro-5H-quinolin-8-one CAS: 129337-86-6, Combi-Blocks
[0052] 2-Methyl-6,7-dihydro-5H-quinolin-8-one CAS: 849643-01-2, Deben Scientific
[0053] Aniline CAS: 62-53-3, Sigma-Aldrich
[0054] p-Toluenesulfonic acid CAS: 104-15-4, Sigma-Aldrich
[0055] Toluene CAS: 108-88-3, Sigma-Aldrich
[0056] Nickel chloride CAS: 7718-54-9, Sigma-Aldrich
[0057] p-Bromoaniline CAS: 106-40-1 Sigma-Aldrich
[0058] 5-Norbornene-2-carboxylic acid methyl ester CAS: 6203-08-3 Leyan Reagent
[0059] 5-Norbornene-2-methylamine CAS No.: 95-10-3 Alfa reagent
[0060] 5-Norbornene-2-olCAS:96185-91-0Sigma-Aldrich
[0061] Palladium chloride CAS: 7647-10-1 Sigma-Aldrich
[0062] Dichloromethane CAS: 75-09-2Siama-Aldrich
[0063] Dimethylsilyl (tert-butylamino) tetramethylcyclopentadienyl titanium dimethyl CAS: 135072-62-7 Sinoco Catalyst
[0064] [Preparatory Example] Preparation of ligands and catalysts
[0065] Preparatory Example 1
[0066]
[0067] Ligand L1 was synthesized as follows: 6,7-Dihydro-5H-quinolin-8-one (1 mmol, 147.2 mg) was dissolved in 50 mL of toluene. 5 μL of p-toluenesulfonic acid (1 mol / L) in DMSO was added as a catalyst. Aniline (1.5 mmol, 139.7 mg) was then added and refluxed at 100°C for 10 hours. After completion of the reaction, the mixture was cooled to room temperature, the solvent was removed by rotary evaporation, and a large amount of ethanol was added to precipitate the crude product. The product was then washed with ethanol and dried in vacuo. The yield was 71%. 1H NMR (400 MHz CDCl3) δ = 8.92 (s, 1HAr-H); δ = 7.75-6.90 (m, 7H Ar-H); δ = 2.84-1.96 (m, 6H-CH2).
[0068]
[0069] Preparation of Ni-based catalyst C1: Ligand L1 (1 mmol, 222.1 mg) and nickel chloride (1.2 mmol, 155.5 mg) were reacted in about 30 mL of acetonitrile solution at room temperature for 12 hours. After the reaction, the mixture was filtered, washed, and dried to obtain catalyst C1 with a yield of 87%.
[0070]
[0071] Preparation of Pd-based catalyst D1: Ligand L1 (1 mmol, 222.1 mg) and palladium chloride (1.2 mmol, 212.8 mg) were reacted in about 30 mL of acetonitrile solution at 40°C for 12 hours. After the reaction, the catalyst was filtered, washed, and dried to obtain catalyst D1 with a yield of 65%.
[0072] Preparatory Example 2
[0073]
[0074] Ligand L2 was synthesized as follows: 2-chloro-6,7-dihydro-5H-quinolin-8-one (1 mmol, 181.6 mg) was dissolved in 40 mL of toluene. 5 μL of 1 mol / L p-toluenesulfonic acid in DMSO was added as a catalyst. Aniline (1.5 mmol, 139.7 mg) was refluxed at 100°C for 12 hours. After the reaction, the mixture was cooled to room temperature, the solvent was removed by rotary evaporation, and a large amount of ethanol was added to precipitate the crude product. The product was then washed with ethanol and dried in vacuo. The yield was 51%. 1H NMR (400 MHz CDCl3) δ = 8.10 (s, 1HAr-H); δ = 7.45-6.93 (m, 6H Ar-H); δ = 2.52-1.91 (m, 6H-CH2).
[0075]
[0076] Preparation of Ni-based catalyst C2: Ligand L2 (1 mmol, 256.7 mg) and nickel chloride (1.2 mmol, 155.5 mg) were reacted in about 30 mL of acetonitrile solution at room temperature for 12 hours. After the reaction, the mixture was filtered, washed, and dried to obtain catalyst C2 with a yield of 69%.
[0077]
[0078] Preparation of Pd-based catalyst D2: Ligand L2 (1 mmol, 256.7 mg) and palladium chloride (1.2 mmol, 212.8 mg) were reacted in about 30 mL of acetonitrile solution at 40°C for 12 hours. After the reaction, the catalyst was filtered, washed, and dried to obtain catalyst D2 with a yield of 46%.
[0079] Preparatory Example 3
[0080]
[0081] Synthesis of ligand L3: 2-methyl-6,7-dihydro-5H-quinolin-8-one (1 mmol, 161.2 mg) was dissolved in 35 ml of toluene solution, followed by the addition of 5 μL of p-toluenesulfonic acid DMSO solution (1 mol / L) as a catalyst, aniline (1.5 mmol, 139.7 mg) was refluxed at 100°C for 12 hours, after the reaction was completed, it was cooled to room temperature, the solvent was removed by rotary evaporation, a large amount of ethanol was added to precipitate the crude product, followed by ethanol washing, and vacuum drying, with a yield of 82%.1H NMR (400 MHz CDCl3) δ = 7.85 (s, 1H Ar-H); δ = 7.42-6.96 (m, 6H Ar-H); δ = 2.71-1.87 (m, 6H-CH2) δ = 2.52 (s, 3H-CH3).
[0082]
[0083] Preparation of Ni-based catalyst C3: Ligand L3 (1 mmol, 236.1 mg) and nickel chloride (1.2 mmol, 155.5 mg) were reacted in about 30 mL of acetonitrile solution at room temperature for 12 hours, after the reaction was completed, it was filtered, washed, and dried to obtain catalyst C3, with a yield of 69%.
[0084]
[0085] Preparation of Pd-based catalyst D3: Ligand L3 (1 mmol, 236.1 mg) and palladium chloride (1.2 mmol, 212.8 mg) were reacted in about 30 mL of acetonitrile solution at 40°C for 12 hours, after the reaction was completed, it was filtered, washed, and dried to obtain catalyst D3, with a yield of 46%.
[0086] Preparation Example 4
[0087]
[0088] Synthesis of ligand L4: 2-methyl-6,7-dihydro-5H-quinolin-8-one (1 mmol, 161.2 mg) was dissolved in 40 ml of toluene solution, followed by the addition of 5 μL of p-toluenesulfonic acid DMSO solution (1 mol / L) as a catalyst, p-bromoaniline (1.5 mmol, 258.0 mg) was refluxed at 100°C for 12 hours, after the reaction was completed, it was cooled to room temperature, the solvent was removed by rotary evaporation, a large amount of ethanol was added to precipitate the crude product, followed by ethanol washing, and vacuum drying, with a yield of 72%.1H NMR (400 MHz CDCl3) δ = 7.82-7.06 (s, 6H Ar-H); δ = 2.73-1.92 (m, 6H-CH2); δ = 2.53 (s, 3H-CH3).
[0089]
[0090] Preparation of Ni-based catalyst C4: ligand L4 (1 mmol, 315.2 mg) was reacted with nickel chloride (1.2 mmol, 155.5 mg) in about 30 mL of acetonitrile solution at room temperature for 12 hours, and after the reaction was completed, the catalyst C4 was obtained by filtration, washing and drying, with a yield of 56%.
[0091]
[0092] Preparation of Pd-based catalyst D4: ligand L4 (1 mmol, 315.2 mg) was reacted with palladium chloride (1.2 mmol, 212.8 mg) in about 30 mL of acetonitrile solution at 40°C for 12 hours, and after the reaction was completed, the catalyst D4 was obtained by filtration, washing and drying, with a yield of 39%.
[0093] Table 1 Catalysts and their preparation raw materials
[0094]
[0095] Note: M is Ni or Pd
[0096] Example 1
[0097] Preparation of polar cyclic olefin copolymer sample 1, the specific steps are as follows: a stainless steel reaction kettle equipped with stirring is used as the reactor, and is baked in an oven for 3 hours before use. About 50 ml of anhydrous toluene solution is added to the reaction kettle as a solvent, followed by the addition of polar cyclic olefin monomer 5-norbornene-2-carboxylic acid methyl ester (10 mmol, 1.52 g), cocatalyst methylaluminoxane MAO (4 mmol), ethylene gas is injected, and the pressure in the reaction kettle is controlled at 0.5 MPa. Then the polymerization temperature is kept at 60°C and the reactants are stirred to mix uniformly, and the reaction is started by adding a toluene solution of total amount of 2 μmol of the main catalyst (molar ratio of catalyst C1 to catalyst D1 is 10:1) through a syringe, and after 3 hours of reaction, the unreacted catalyst is quenched with 10% HC1-MeOH solution, and the obtained polymer is filtered, washed with ethanol, and vacuum dried to obtain polar cyclic olefin copolymer sample 1.
[0098] Example 2
[0099] Polar cycloolefin copolymer Sample 2 was prepared as follows: a stainless steel reactor equipped with a stirrer was used as the reactor and oven-baked for 3 hours before use. Approximately 55 ml of anhydrous toluene solution was added to the reactor as the solvent, followed by the addition of the polar cycloolefin monomer methyl 5-norbornene-2-carboxylate (10 mmol, 1.52 g) and the cocatalyst methylaluminoxane (MAO) (3 mmol). Ethylene gas was then injected, and the reactor pressure was controlled at 0.6 MPa. The polymerization temperature was then maintained at 60°C with stirring to ensure uniform mixing. A total of 2 μmol of a toluene solution of the primary catalyst (catalyst C2 and catalyst D2 in a molar ratio of 10:1.5) was added via syringe to initiate the reaction. After 2.5 hours of reaction, unreacted catalyst was quenched with a 10% HCl-MeOH solution. The resulting polymer was filtered, washed with ethanol, and vacuum-dried to obtain Polar cycloolefin copolymer Sample 2.
[0100] Example 3
[0101] Polar cycloolefin copolymer sample 3 was prepared as follows: a stainless steel reactor equipped with a stirrer was used as the reactor and oven-baked for 3 hours before use. Approximately 50 ml of anhydrous toluene solution was added to the reactor as the solvent, followed by the addition of the polar cycloolefin monomer 5-norbornene-2-carboxylic acid methyl ester (10 mmol, 1.52 g) and the cocatalyst methylaluminoxane (MAO) (4 mmol). Ethylene gas was then injected, and the pressure in the reactor was controlled at 0.35 MPa. The polymerization temperature was then maintained at 65°C and stirred to uniformly mix the reactants. A total of 2 μmol of the main catalyst (catalyst C3 and catalyst D3 in a molar ratio of 10:1.5) in toluene was added via syringe to initiate the reaction. After 3 hours of reaction, the unreacted catalyst was quenched with a 10% HCl-MeOH solution. The resulting polymer was filtered, washed with ethanol, and vacuum-dried to obtain polar cycloolefin copolymer sample 3.
[0102] Example 4
[0103] Preparation of polar cyclic olefin copolymer sample 4, the specific steps are as follows: a stainless steel reactor equipped with stirring is used as the reactor, and is baked in an oven for 3 hours before use. About 65 ml of anhydrous toluene solution is added to the reactor as a solvent, followed by the addition of polar cyclic olefin monomer 5-norbornene-2-carboxylic acid methyl ester (10 mmol, 1.52 g), co-catalyst methylaluminoxane MAO (4 mmol), ethylene gas is injected, and the pressure in the reactor is controlled at 0.45 MPa. Then the polymerization temperature is kept at 70°C and the reactants are stirred to mix uniformly, the reaction is started by adding a toluene solution of a total amount of 2 μmol of the main catalyst (molar ratio of catalyst C4 to catalyst D4 is 10:2) through a syringe, after 3 hours of reaction, the unreacted catalyst is quenched with 10% HC1-MeOH solution, the obtained polymer is filtered, ethanol washed, vacuum dried, and polar cyclic olefin copolymer sample 4 is obtained.
[0104] Example 5
[0105] Preparation of polar cyclic olefin copolymer sample 5, the specific steps are as follows: a stainless steel reactor equipped with stirring is used as the reactor, and is baked in an oven for 3 hours before use. About 60 ml of anhydrous toluene solution is added to the reactor as a solvent, followed by the addition of polar cyclic olefin monomer 5-norbornene-2-methylamine (10 mmol, 1.24 g), co-catalyst methylaluminoxane MAO (4 mmol), ethylene gas is injected, and the pressure in the reactor is controlled at 0.5 MPa. Then the polymerization temperature is kept at 65°C and the reactants are stirred to mix uniformly, the reaction is started by adding a toluene solution of a total amount of 2 μmol of the main catalyst (molar ratio of catalyst C2 to catalyst D3 is 10:1.5) through a syringe, after 3 hours of reaction, the unreacted catalyst is quenched with 10% HC1-MeOH solution, the obtained polymer is filtered, ethanol washed, vacuum dried, and polar cyclic olefin copolymer sample 5 is obtained.
[0106] Example 6
[0107] Polar cycloolefin copolymer sample 6 was prepared as follows: a stainless steel reactor equipped with a stirrer was used as the reactor and oven-baked for 3 hours before use. Approximately 55 ml of anhydrous toluene solution was added to the reactor as the solvent, followed by the addition of the polar cycloolefin monomer 5-norbornene-2-methylamine (10 mmol, 1.24 g) and the cocatalyst methylaluminoxane (MAO) (4 mmol). Ethylene gas was then injected, and the reactor pressure was controlled at 0.45 MPa. The polymerization temperature was then maintained at 60°C with stirring to ensure uniform mixing. A total of 2 μmol of the main catalyst (catalyst C3 and catalyst D2 in a 10:2 molar ratio) in toluene was added via syringe to initiate the reaction. After 3 hours of reaction, unreacted catalyst was quenched with a 10% HCl-MeOH solution. The resulting polymer was filtered, washed with ethanol, and vacuum-dried to obtain polar cycloolefin copolymer sample 6.
[0108] Example 7
[0109] Polar cycloolefin copolymer sample 7 was prepared as follows: a stainless steel reactor equipped with a stirrer was used as the reactor and oven-baked for 3 hours before use. Approximately 50 ml of anhydrous toluene solution was added to the reactor as the solvent, followed by the addition of the polar cycloolefin monomer 5-norbornene-2-ol (10 mmol, 1.96 g) and the cocatalyst methylaluminoxane (MAO) (3.5 mmol). Ethylene gas was then injected, and the pressure in the reactor was controlled at 0.5 MPa. The polymerization temperature was then maintained at 60°C and stirred to uniformly mix the reactants. A total of 2 μmol of the main catalyst (catalyst C2 and catalyst D4 in a 10:1 molar ratio) in toluene was added via syringe to initiate the reaction. After 2.5 hours of reaction, the unreacted catalyst was quenched with a 10% HCl-MeOH solution. The resulting polymer was filtered, washed with ethanol, and vacuum-dried to obtain polar cycloolefin copolymer sample 7.
[0110] Example 8
[0111] The preparation of polar cycloolefin copolymer sample 8 was carried out as follows: a stainless steel reactor equipped with a stirrer was used as the reactor and baked in an oven for 3 hours before use. Approximately 50 ml of anhydrous toluene solution was added to the reactor as the solvent, followed by the addition of the polar cycloolefin monomer 5-norbornene-2-carboxylic acid methyl ester (10 mmol, 1.52 g) and the co-catalyst methylaluminoxane (MAO) (5 mmol). Ethylene gas was then injected, and the pressure in the reactor was controlled to 0.45 MPa. The polymerization temperature was then maintained at 70°C and stirred to uniformly mix the reactants. A total of 2 μmol of a toluene solution of the main catalyst (catalyst C4 and catalyst D3 in a molar ratio of 10:1.5) was added via syringe to initiate the reaction. After 3.5 hours of reaction, the unreacted catalyst was quenched with a 10% HCl-MeOH solution. The resulting polymer was filtered, washed with ethanol, and vacuum dried to obtain polar cycloolefin copolymer sample 8.
[0112] Comparative Example 1
[0113] Preparation of cycloolefin copolymer sample a: With reference to Example 2, catalyst C2 is used alone as the main catalyst. The specific steps are as follows: A stainless steel reactor equipped with stirring is used as the reactor and baked in an oven for 3 hours before use. About 55 ml of anhydrous toluene solution is added to the reactor as a solvent, followed by the addition of polar cycloolefin monomer 5-norbornene-2-carboxylic acid methyl ester (10 mmol, 1.52 g) and co-catalyst methylaluminoxane MAO (3 mmol), ethylene gas is injected, and the pressure in the reactor is controlled to 0.6 MPa. The polymerization temperature is then maintained at 60°C and stirred to mix the reactants evenly. A toluene solution containing 2 μmol of catalyst C2 is added via a syringe to initiate the reaction. After 3 hours of reaction, the unreacted catalyst is quenched with a 10% HCl-MeOH solution. The resulting polymer is filtered, washed with ethanol, and vacuum dried to obtain a cycloolefin copolymer sample a.
[0114] Comparative Example 2
[0115] Preparation of Cyclic Olefin Copolymer Sample b: Using Example 2 as a reference, Catalyst D2 was used alone as the primary catalyst. The specific steps were as follows: A stainless steel reactor equipped with a stirrer was used as the reactor and oven-baked for 3 hours before use. Approximately 55 ml of anhydrous toluene solution was added to the reactor as the solvent. The polar cycloolefin monomer, methyl 5-norbornene-2-carboxylate (10 mmol, 1.52 g), and the cocatalyst, methylaluminoxane (MAO) (3 mmol), were then added. Ethylene gas was injected, and the pressure in the reactor was controlled at 0.6 MPa. The polymerization temperature was then maintained at 60°C with stirring to uniformly mix the reactants. A toluene solution containing 2 μmol of Catalyst D2 was added via syringe to initiate the reaction. After 4 hours of reaction, unreacted catalyst was quenched with a 10% HCl-MeOH solution. The resulting polymer was filtered, washed with ethanol, and vacuum-dried to obtain Cyclic Olefin Copolymer Sample b.
[0116] Comparative Example 3
[0117] Preparation of Cyclic Olefin Copolymer Sample C: Using Example 2 as a reference, the main catalyst was replaced with a commercially available CGC-type catalyst (dimethylsilyl(tert-butylamino)tetramethylcyclopentadienyldimethyltitanium). The specific steps were as follows: A stainless steel reactor equipped with a stirrer was used as the reactor and baked in an oven for 3 hours before use. Approximately 55 ml of anhydrous toluene solution was added to the reactor as the solvent, followed by the addition of polar cycloolefin monomer 5-norbornene-2-carboxylic acid methyl ester (10 mmol, 1.52 g) and cocatalyst methylaluminoxane (MAO) (3 mmol). Ethylene gas was injected, and the pressure in the reactor was controlled to 0.6 MPa. The polymerization temperature was then maintained at 60°C with stirring to uniformly mix the reactants. A toluene solution containing 2 μmol of the CGC-type catalyst was added via syringe to initiate the reaction. After 3 hours of reaction, the unreacted catalyst was quenched with a 10% HCl-MeOH solution. The resulting polymer was filtered, washed with ethanol, and vacuum-dried to obtain Cyclic Olefin Copolymer Sample C.
[0118]
Catalyst activity test
[0119] The catalyst activity was calculated based on the copolymer yield, in terms of g copolymer / (mol catalyst×h). Table 2 lists the catalytic activities of the examples and comparative examples.
[0120] Table 2 Catalytic activity of catalysts
[0121] Serial number catalyst Catalytic activity (g / mol·h) Example 1 C1+D1(10:1) <![CDATA[6.1×10 5 ]]> Example 2 C2+D2(10:1.5) 1.03 x 10 6 ]] Example 3 C3+D3(10:1.5) <![CDATA[7.7×10 5 ]]> Example 4 C4+D4(10:2) <![CDATA[9.24×10 5 ]]> Example 5 C2+D3(10:1.5) <![CDATA[8.9×10 5 ]]> Example 6 C3+D2(10:2) <![CDATA[8.4×10 5 ]]> Example 7 C2+D4(10:1) <![CDATA[9.9×10 5 ]]> Example 8 C4+D3(10:1.5) <![CDATA[8.8×10 5 ]]> Comparative Example 1 C2 <![CDATA[4.6×10 5 ]]> Comparative Example 2 D2 <![CDATA[6×10 4 ]]> Comparative Example 3 CGC <![CDATA[3.85×10 5 ]]>
[0122] As can be seen from Table 2, the late transition nickel catalyst and the late transition palladium catalyst in the embodiment of the present invention can effectively promote the copolymerization reaction of polar comonomers and ethylene, and the catalytic activity is much higher than that of Comparative Example 1 and Comparative Example 2 of a single catalyst, and higher than that of the commercially available CGC catalyst, indicating that the composite catalyst has better catalytic performance than the traditional CGC catalyst in the polar cycloolefin copolymerization system.
[0123]
Cyclic olefin copolymer performance test
[0124] The performance tests of some of the cyclic olefin copolymer samples obtained above were carried out, including:
[0125] 1. Molecular weight determination: Determined by gel permeation chromatography in accordance with GB / T 27843-2011 "Determination of low molecular weight components in polymers - Gel permeation chromatography (GPC)";
[0126] 2. Determination of cycloolefin monomer content: calculated using the H-NMR spectrum of the copolymer product;
[0127] 3. Determination of glass transition temperature (Tg): According to GB / T 19466.2-2004: Plastics Differential Scanning Calorimetry (DSC) Part 2: Determination of glass transition temperature.
[0128] Table 3 Performance of Examples and Comparative Examples
[0129]
[0130] Note: “—” means not tested.
[0131] As shown in Table 3, the weight-average molecular weights of the copolymers obtained in the Examples were all greater than 100,000, indicating that the Examples were able to produce high-molecular-weight polymers using the polar cycloolefin catalyst system, while Comparative Examples 2 and 3 failed to successfully produce high-molecular-weight polymers. The PDI range for the Examples was 2.1–2.5, with a relatively narrow overall distribution (<2.5), indicating a relatively uniform distribution of active centers in the composite catalyst and good controllability of the polymerization process. In terms of polar comonomer insertion rate, the polar comonomer content in the Examples remained above 10%, significantly higher than that in the Comparative Examples. The polar comonomer content in Comparative Example 1 was essentially zero, indicating that a single nickel catalyst was unable to promote the participation of polar cycloolefins in copolymerization. The polar cycloolefin insertion rate in Comparative Example 3 was significantly lower than that in the Examples, indicating that conventional CGC catalysts are extremely inefficient in catalyzing the copolymerization of polar cycloolefin monomers with ethylene. The catalytic system of the present invention, while maintaining a high cycloolefin insertion rate, can produce polar cycloolefin polymers with high molecular weight, narrow distribution, and high Tg, demonstrating promising application prospects.
[0132] The foregoing description of the embodiments has been presented for the purpose of illustration and description. It is not intended to be exhaustive or to limit the application to the precise form disclosed. Modifications and variations are possible in light of the above teachings or can be acquired from practice of the application. As well, the description is presented in the context of the preferred embodiments as a number of alternatives. It is not intended to limit the application to the precise form described.
Claims
1. A method for preparing a polar cycloolefin copolymer, characterized in that: In an inert solvent, ethylene and polar cycloolefin monomers are used as raw materials to carry out copolymerization reaction by using a catalyst composition, wherein the catalyst composition comprises: a late transition nickel catalyst, a late transition palladium catalyst and a co-catalyst. The structural formula of the late transition nickel catalyst is shown in Formula C, and the structural formula of the late transition palladium catalyst is shown in Formula D: In formula C and formula D, X is chlorine or bromine, R1 to R9 are independently selected from H, C1 to C6 alkyl, C1 to C6 alkoxy, C6 to C 12 Aryl or halogen.
2. The method for preparing a polar cycloolefin copolymer according to claim 1, wherein In Formula C and Formula D, at least one of R1 to R9 is selected from H, C1-C6 alkyl or halogen.
3. The method for preparing a polar cycloolefin copolymer according to claim 2, wherein: In Formula C and Formula D, at least one of R1 and R9 is a C1-C6 alkyl group or a halogen, and the halogen is selected from F, Cl, Br, and I.
4. The method for preparing a polar cycloolefin copolymer according to claim 1, wherein The late transition nickel catalyst is selected from any one of the following formulas C1 to C4, and the late transition palladium catalyst is selected from any one of the following formulas D1 to D4: Wherein, X is chlorine or bromine.
5. The method for preparing a polar cycloolefin copolymer according to any one of claims 1 to 4, characterized in that: The late transition nickel catalyst and the late transition palladium catalyst are prepared by reacting an α-diimine ligand represented by formula L with a nickel salt or a palladium salt in an anhydrous aprotic organic solvent under an anhydrous and oxygen-free environment.
6. The method for preparing a polar cycloolefin copolymer according to claim 5, characterized in that: The α-diimine ligand represented by Formula L is prepared by acid catalysis using a 6,7-dihydro-5H-quinolin-8-one derivative of the general structure represented by Formula I and an aniline derivative of the general structure represented by Formula II as raw materials. The specific reaction formula is as follows:
7. The method for preparing a polar cycloolefin copolymer according to claim 1, wherein: The molar ratio of the late transition nickel catalyst, the late transition palladium catalyst and the co-catalyst is 1:0.05-0.5:50-10000; Preferably, the molar ratio of the late transition nickel catalyst, the late transition palladium catalyst and the co-catalyst is 1:0.08-0.25:200-6000; Further preferably, the molar ratio of the late transition nickel catalyst, the late transition palladium catalyst and the co-catalyst is 1:0.1-0.2:200-3000.
8. The method for preparing a polar cycloolefin copolymer according to claim 1, wherein: The inert solvent includes C6-C8 straight-chain alkanes, benzene and its derivatives, preferably benzene, toluene, xylene, chlorobenzene, hexane, and pentane; and / or, the polar cycloolefin monomer is a cycloolefin with a polar group, including 5-norbornene-2-carboxylic acid methyl ester, 5-norbornene-2-ol, 5-norbornene-2-methylamine, 5-norbornene-2,3-dicarboxylic acid methyl ester, 5-norbornene-2-carboxylic acid, and 5-methoxy-2-norbornene; and / or, the cocatalyst comprises an alkylaluminoxane; And / or, during the copolymerization reaction, a temperature-controlled pressure-resistant reactor is used as the reactor, and the pressure in the reactor is controlled to be 0.1-10 MPa and the temperature is controlled to be 50-120° C. by ethylene; and / or, the volume molar ratio of the inert solvent to the polar cycloolefin monomer is 1-10 L / mol, preferably 2-8 L / mol, more preferably 4-6 L / mol; And / or, the molar ratio of the total amount of the late transition nickel catalyst and the late transition palladium catalyst to the polar cycloolefin monomer is 0.01% to 1%, preferably 0.01% to 0.1%, and more preferably 0.01% to 0.05%.
9. A polar cycloolefin copolymer, characterized in that The method is described in any one of claims 1 to 8.
10. Use of the polar cycloolefin copolymer according to claim 9 in the preparation of electronic display materials, medical or pharmaceutical packaging materials.